SERUM VITAMIN D IN PATIENTS WITH BENIGN, PRIMARY MALIGNANT AND METASTATIC BONE TUMORS - Drobotun, Oleg; Ternovy, Мykola; Kolotilov, Мykola (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
Participant in the process of normal bone remodeling is vitamin D, which, in addition, has antiinflammatory (anti-cytokine), anti-proliferative and anti-tumor effects. Objective of the study is to assess the level of 25-hydroxyvitamin D3 concentration in blood serum before the start of treatment in patients with benign, primary malignant and metastatic bone tumors, taking into account polymorbidity. Materials and methods. The following patients were included in the study: 21 patients with benign pelvic bone tumors; 52 patients with malignant tumors of the bones of the pelvis and lower limbs; 52 patients with metastatic tumors of the bones of the pelvis and lower limbs. The control group consisted of 22 practically healthy volunteers without chronic diseases. The content of vitamin D was determined by the immunochemiluminescence method. The results. The content of vitamin D in blood serum in patients with benign bone tumors is in the range from 22.4 to 29.6 ng/ml, with primary malignant tumors — from 7.8 to 15.9 ng/ml, with metastatic ones — from 13.8 to 15.5 ng/ml. There are no statistically significant differences between the histotypes of primary malignant bone tumors (p > 0.05). Conclusions. Polymorbidity statistically significantly increases vitamin D deficiency in patients with osteogenic sarcoma and patients with metastatic bone tumors (p < 0.05). According to the national classification of vitamin D content, patients with benign bone tumors have a suboptimal level of vitamin D, while patients with primary malignant and metastatic bone tumors have vitamin D deficiency.